2021
DOI: 10.3390/microorganisms9102110
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing the Early Life Gut Microbiome and Immune Maturation for Long Term Health

Abstract: Early life is characterized by developmental milestones such as holding up the head, turning over, sitting up and walking that are typically achieved sequentially in specific time windows. Similarly, the early gut microbiome maturation can be characterized by specific temporal microorganism acquisition, colonization and selection with differential functional features over time. This orchestrated microbial sequence occurs from birth during the first years of age before the microbiome reaches an adult-like compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 156 publications
0
41
0
2
Order By: Relevance
“…Bifidobacterium longum subspecies are a ubiquitous presence in the gut microbiota of human infants, transmitted vertically from the mother at birth via vaginal delivery or shortly after in the first breastmilk meals and thereupon proliferating by metabolizing the HMOs consumed through subsequent breastfeeding ( 41 , 42 ). Metabolites produced by this fermentation process, such as acetate, formate and lactate, promote epithelial barrier function ( 43 ) and create an acidic environment hostile to bacterial pathogens ( 44 ), while the adhesion of enterocytes to bifidobacterial interacting with pilis and other surface-associated cellular structures trigger some of the first proinflammatory responses, priming the immune system for early development ( 8 , 41 , 45 ). These processes are believed to underly the well-documented associations of intestinal bifidobacterial colonization with numerous health benefits later in infancy and beyond ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium longum subspecies are a ubiquitous presence in the gut microbiota of human infants, transmitted vertically from the mother at birth via vaginal delivery or shortly after in the first breastmilk meals and thereupon proliferating by metabolizing the HMOs consumed through subsequent breastfeeding ( 41 , 42 ). Metabolites produced by this fermentation process, such as acetate, formate and lactate, promote epithelial barrier function ( 43 ) and create an acidic environment hostile to bacterial pathogens ( 44 ), while the adhesion of enterocytes to bifidobacterial interacting with pilis and other surface-associated cellular structures trigger some of the first proinflammatory responses, priming the immune system for early development ( 8 , 41 , 45 ). These processes are believed to underly the well-documented associations of intestinal bifidobacterial colonization with numerous health benefits later in infancy and beyond ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immune system of the intestinal mucosa consists of lymph nodes, lamina propria, and epithelial cells that form a physiological barrier that protects the integrity of the gut ( Shi et al., 2017 ). Innate immune cells use a diversity of PRRs, including Toll-like receptors, NOD-like receptors and leptin-like receptors, to recognize conserved molecular patterns of microbes and signaling of these receptors may then act as developmental triggers for the gut microbiome ( Fulde et al., 2018 ; Price et al., 2018 ; Dogra et al., 2021 ). IL-22 produced by innate lymphoid cells is in a position to induce hRegIIIα production in epithelial cells, which binds to bacterial peptidoglycan carbohydrates and kills Gram-positive target bacteria ( Mukherjee et al., 2014 ; Shi et al., 2017 ).…”
Section: Infant Immune System Regulates the Composition Of Gut Microb...mentioning
confidence: 99%
“…Changing the structure, abundance, and eubiotic state of the microbiota may contribute to intestinal and parenteral autoimmune and inflammatory disorders [12,30], which can lead to the occurrence of diseases associated with these conditions. It has been suggested that this condition could be the result of a lack of early stimulation of the immune system by biotic factors, which may interfere with the functioning of the immune system later in life and lead to hypersensitivity, autoimmune diseases, and/or inflammatory diseases [31]. This could explain the fact that there are more and more cases of autoimmune diseases, the occurrence of which cannot always be explained by genetic factors, but rather environmental factors, e.g., T1DM [5].…”
Section: The Importance Of Microbiota For Human Healthmentioning
confidence: 99%
“…Questionable lifestyle and nutritional choices (albeit not always intentional), primarily in developed countries characterized by the West-type diet, may lead to the development of microbiota that lack the immunity and diversity necessary for a balanced immune response. It is believed that this may lead to an increase in autoimmune and inflammatory diseases [31,73]. Increased consumption of junk food has been shown to be associated with less gut microbiome diversity in children with T1DM [74].…”
Section: Diet Components Positively Influencing the Development Of Mi...mentioning
confidence: 99%